PAAPPAS community trial protocol: a randomized study of obesity prevention for adolescents combining school with household intervention - Michele R. Sgambato; Diana B. Cunha; Viviana T. Henriques; Camilla C. P. Estima; Bárbara S. N. Souza; Rosangela A. Pereira; Edna M. Yokoo; Vitor B. Paravidino; Rosely Sichieri (BMC Public Health, 2016)
Abstract Background The prevalence of childhood obesity is increasing at a high rate in Brazil, making prevention a health priority. Schools are the central focus of interventions aiming the prevention and treatment of childhood obesity, however, randomized trials and cohort studies have not yet provided clear evidence of strategies to reduce prevalence of obesity. The aim of this study is to present a protocol to evaluate the efficacy of combining school and household level interventions to reduce excessive weight gain among students. Methods The intervention target fifth and sixth graders from 18 public schools (9 interventions and 9 controls) in the municipality of Duque de Caxias, metropolitan area of Rio de Janeiro, Brazil. A sample size of 2500 students will be evaluated at school for their weight status and those from the intervention group who are overweight or obese will be followed monthly at home by community health agents. Demographic, socioeconomic, anthropometric, eating behavior and food consumption data will be collected at school using a standardized questionnaire programmed in personal digital assistant. At school, all students from the intervention group will be encouraged to change eating habits and food consumption and to increase physical activity and reducing sedentary behavior. Discussion This study will provide evidence whether integration of school with primary health care can prevent excessive weight gain among adolescents. Positive results will inform a sustainable strategy to be disseminated in the health care system in Brazil. Trial registration ClinicalTrials.gov, NCT02711488 . Date of registration: March 11, 2016.